Phosphorescence within benzotellurophenes and color tunable tellurophenes under ambient conditions. Issue 25 (31st October 2014) - He, Gang; Wiltshire, Benjamin D.; Choi, Paul; Savin, Aliaksandr; Sun, Shuai; Mohammadpour, Arash; Ferguson, Michael J.; McDonald, Robert; Farsinezhad, Samira; Brown, Alex; Shankar, Karthik; Rivard, Eric
Abstract : The zirconium-mediated syntheses of pinacolboronate (BPin) appended benzo[ b ]tellurophenes and two phenyl/BPin substituted tellurophene isomers with different colors of emission have been achieved. Abstract : The zirconium-mediated syntheses of pinacolboronate (BPin) appended benzo[ b ]tellurophenes and two phenyl/BPin substituted tellurophene isomers with different colors of emission have been achieved. These species are new additions to an emerging class of inorganic heterocycles that display visible phosphorescence in the solid state under ambient conditions.